Child marriages - Nazli Hossain (Journal of the Pakistan Medical Association, 2023)
Child marriages are major public health issues in the developing world. It is defined as marriage before the age of 18 years. According to UNFPA (United Nations Fund for Population), in developing world, 36 percent of girls are married before reaching the age of 18 years, and 10 percent of girls in these countries are married before the age of 15 years.1 Globally, it is estimated that 10 million pregnancies occur in adolescent girls, and 90% of these occur in developing countries.2 The burden is mainly borne by the Sub Saharan Africa and South Asian countries.3 Except in Nepal, where legal age of marriage is 20 years, the legal age in India, Bangladesh and Srilanka is 18 years. In Pakistan, except for the Sindh province where legal age of marriage is 18 years, the rest of the provinces have legal age of 16 years for contracting marriage. Hence there is increased prevalence of child marriage in Baluchistan and Khyber Pakhtunkhwa provinces.4 It is observed that this legal cover is mainly seen on papers, and reality is far different in the actual world. Child marriages not only take away the joys of childhood, it also brings with it the burden of social, psychological and reproductive harms. It not only affects the female child, but also has its effects on the male child. The burden of raising and supporting a family at a younger age exerts extra mental and psychological trauma, among boys. This in turn increases the incidence of domestic violence among the couples. It is a well-known fact that child marriages are more common in low- income household, rural areas, and at times are contracted in order to settle family disputes. In rural areas these child marriages are seen as a stop gap arrangement for premarital sex, unwanted pregnancies and sexual assault. These adolescent girls are married to elderly men, invoking mental disparity and psychological trauma. There is also increased prevalence of domestic violence and wife beating in this age group. Vertical transmission of this attitude has also been observed in studies. This basic violation of human rights is transferred from mothers to daughters as normal behaviours.5 Continue...